A Soft Wire Chinese Finger Grip - Satya Prakash (Indian Journal of Plastic Surgery)
The soft wire Chinese finger grip offers a convenient mode of applying traction on fingers, pulling them apart if necessary and helps in application of plaster case in the region. It can also be used for suspending the upper limb during surgery and for elevation of the hand. It is durable and can be easily sterilized. It is almost inexpensive and has been used by the author for more than 25 years without any regrets.